Application of Android-based Learning Media Applications for Primary Education - Andri; Somawati (Cattleya Darmaya Fortuna, 2024)
Today's learning media has improved considerably than ever before and English at this time is a very important need because English has become an International language. As a means of supporting these activities, cellular phones (cellphones) can be used where currently there are many people from various circles who own and use them. For this reason, researchers created an English learning media application for children based on multimedia and smartphones that is expected to support learning activities and be easy for children to understand. This application contains basic English materials, such as introduction to alphabets, families, numbers and others. This application is equipped with animated images and how to pronounce them in English as well as practice questions for learning the material. By using the Android platform, with this application, it is hoped that children can better understand material about English. The creation of this android-based English learning application uses Adobe Flash CS5 and Adobe Photoshop CS5 software to design application designs. The software used in the creation of this application is Android-SDK (Software Development Kit), JDK (Java Development Kit) installation package, Eclipse Indigo and this application is tested on Android emulators and some android smartphones.